Analysis of Factors Influencing Acceptance of the Online Population Administration Information System in Mojokerto Regency Using Technology Acceptance Model (TAM 3) - AYER, FIDIANTI RAMADANI SUHADI; Indriyanti, Aries Dwi (Universitas Negeri Surabaya, 2024)
This research investigates factors influencing the acceptance of the POSKeTanMu online population administration system in Mojokerto Regency using the Technology Acceptance Model (TAM 3). POSKeTanMu (Pelayanan Online Sistem Kependudukan Tanpa Ketemu) is a self-service online population administration system for residents of Mojokerto Regency. A quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied, analyzing data from 159 respondents through questionnaires. Findings indicate that Behavioral Intention (BI) significantly influences user independence and responsibility. Key factors affecting technology acceptance include perceived usefulness, ease of use, social influence, and experience, while computer anxiety and system usability showed no significant impact. Additionally, the study explores the implementation of the Double Track program using a qualitative case study approach, guided by Thomas Lickona’s character-building theory. Data collection involved interviews, observations, and documentation, analyzed using Miles and Huberman’s framework. Results highlight ease of use, perceived benefits, and social perceptions as major drivers of technology adoption. Positive user experiences and social support play crucial roles in enhancing e-government adoption. This research contributes to the development of POSKeTanMu and provides strategic recommendations for the government to strengthen digital service implementation. Findings offer valuable insights for policy formulation to improve e-government services and promote broader technology adoption in society.